The dynamics and processes of writing the 1987 Constitution - Villacorta, Wilfrido V. (1988)
The process of framing the 1987 Constitution illustrates a close relationship between constitution-making and economic class interests. This is also true when the 1899, 1935 and the 1973 Constitutions were still being framed, if one would consider the visible as well as the "invisible" forces that influenced the decisions of many of the Commissioners and the ideological foundations of the political dispensation. Notwithstanding such an occurrence, the new Constitution contains saving features that can usher the country forward.
Keywords: Constitutional law; 1987 Philippine Constitution